Effect of Yashtimadhu Suppository with Cocoa Butter Base in the Pain Management of Parikartika (International Journal of Ayurveda and Pharma Research, 2022)
Parikartika is one of the common ano-rectal anomalies observed in clinical practise. In Ayurveda Samhitas, this condition is mostly mentioned as an Upadrava of Grahani, Atisara, Arshas and as Vamanavirechanavyapat. ‘Kartanavatvedhana’ is described as predominant symptom of Parikartika which means cutting type of pain in the anus. As per the description of signs and symptoms, Parikartika can be co-related to fissure-in ano in modern contexts. Yashtimadhu is the most widely used drug for Parikartika. Acharya Susruta has mentioned the drug Yashtimadhu in Trividhakarma Adhyaya in post-operative pain management and in treatment for Parikartika in Vamana virechana vyapat. Yashtimadhu in the form of Thaila and Ghrita are commonly used. Here, Yashtimadhuchurna was used to prepare a suppository with cocoa butter as its base for the management of Parikartika. Objectives: The objective of the clinical study is to evaluate any difference in the efficacy of Yashtimadhu suppository in treating Parikartika. Materials and Methods: The study was conducted as an open labelled, randomized, single arm clinical study. 40 Patients who are fulfilling the inclusion, exclusion, diagnostic criteria and complying with the informed consent was selected from OPD and IPD of Sri Jayendra Saraswathi Ayurveda College and Hospital [IEC NO- IEC/ SJSACH/ 09/2021, CTRI NO- CTRI/2021/07/035252]. Case proforma was prepared with all the appropriate details of the patient along with history and physical, rectal examination was done to diagnose Parikartika. Relevant laboratory investigations were performed. Yashtimadhu suppository was given twice per day for about 14 days to 40 patients along with 4 follow-ups once a week for one month after the treatment i.e., 7th, 14th, 21st, 28th day. The subjective parameter was pain and objective parameter were ulceration, sphincter tone. Grading was done according to the specified assessment criteria and was statistically analysed. Results: On completion of the study, statistical analysis was done on the data collected. The intervention, Yashtimadhu suppository showed significant difference in the outcome.